Bibliotheca Dissidentium XXIX: The Family of Love II: Hiël (Hendrik Jansen van Barrefelt) - Rothkegel, Martin (Verlag Valentin Koerner GmbH, 2013)
In the 16th century, a certain number of individuals, isolated or gathered in groups, remained outside the traditional Church and the churches established following the Lutheran, Zwinglian, Bucerian, and Calvinist Reformations. They were referred to by a wide variety of terms: Radicals, Nonconformists, the left wing of the Reformation, and dissidents. In fact, none of these terms is entirely satisfactory, particularly because behind the dissidence lie very diverse tendencies, ranging from a highly communitarian Anabaptism to various forms of individualistic spiritualism, often with very different motivations. In the 17th century, religious dissidence changed its motivation; it resulted less from a protest against orthodoxies than from the desire to explain the world and its religion differently, combined with a natural philosophy. This volume presents a biographical sketch an an annotated bibliography of Hendrik Jansen van Barrefelt aka Hiël Ab 21: In the 16th century, a certain number of individuals, isolated or gathered in groups, remained outside the traditional Church and the churches established following the Lutheran, Zwinglian, Bucerian, and Calvinist Reformations. They were referred to by a wide variety of terms: Radicals, Nonconformists, the left wing of the Reformation, and dissidents. In fact, none of these terms is entirely satisfactory, particularly because behind the dissidence lie very diverse tendencies, ranging from a highly communitarian Anabaptism to various forms of individualistic spiritualism, often with very different motivations. In the 17th century, religious dissidence changed its motivation; it resulted less from a protest against orthodoxies than from the desire to explain the world and its religion differently, combined with a natural philosophy. This volume presents a biographical sketch an an annotated bibliography of Hiël (Hendrik Jansen van Barrefelt)